2006
DOI: 10.1007/s11423-006-9003-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a cognitive tool that helps students learn diagnostic problem solving

Abstract: Three related studies replicated and extended previous work ( J.A. Danielson et al. (2003),Educational Technology Research and Development, 51(3), 63-81) involving the Diagnostic Pathfinder (dP) (previously Problem List Generator [PLG]), a cognitive tool for learning diagnostic problem solving. In studies 1 and 2, groups of 126 and 113 veterinary students, respectively, used the dP to complete case-based homework; groups of 120 and 199, respectively, used an alternative method. Students in the dP groups scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Similarly, students using the Pathfinder as a supplemental instructional strategy also outscored their counterparts participating in otherwise identical instruction [7]. Students also indicated that using the Pathfinder made their homework more enjoyable and made learning clinical pathology easier [5,7]. These results have been consistent across thousands of students at seven veterinary colleges where evaluations have been performed one or more times (depending on the college) between 2002 and 2010.…”
Section: Research Results and Theoretical Foundations-why It Workmentioning
confidence: 66%
See 3 more Smart Citations
“…Similarly, students using the Pathfinder as a supplemental instructional strategy also outscored their counterparts participating in otherwise identical instruction [7]. Students also indicated that using the Pathfinder made their homework more enjoyable and made learning clinical pathology easier [5,7]. These results have been consistent across thousands of students at seven veterinary colleges where evaluations have been performed one or more times (depending on the college) between 2002 and 2010.…”
Section: Research Results and Theoretical Foundations-why It Workmentioning
confidence: 66%
“…We found that students who used the Pathfinder performed significantly better on case-based final exam questions than those who participated in curricular processes that used paper-based cases but were otherwise identical (Table 2) [5,7]. Similarly, students using the Pathfinder as a supplemental instructional strategy also outscored their counterparts participating in otherwise identical instruction [7]. Students also indicated that using the Pathfinder made their homework more enjoyable and made learning clinical pathology easier [5,7].…”
Section: Research Results and Theoretical Foundations-why It Workmentioning
confidence: 83%
See 2 more Smart Citations
“…Feedback that addresses learner misconceptions can be provided when erroneous solution paths are identified. Examples of the use of novice-expert overlay models to promote expertise in clinical reasoning include the Diagnostic Pathfinder (Danielson et al, 2007), the NUDOV system (Wahlgren, Edelbring, Fors, Hindbeck, & Stahle, 2006), and BioWorld (Lajoie et al, 2013(Lajoie et al, , 2015. In this study, we extended the prior analytics methods we used with BioWorld to analyze learner actions in the more widely-used MedU online learning environment.…”
Section: Detecting Misconceptions In Online Learningmentioning
confidence: 99%